Tailoring Potential Natural Compounds for the Treatment of Luminal Breast Cancer - Fernanda Cardoso da Silva; Douglas Cardoso Brandão; Everton Allan Ferreira; Raoni Pais Siqueira; Helen Soares Valença Ferreira; Ademar Alves Da Silva Filho; Thaise Gonçalves Araújo (MDPI AG, 2023)
Breast cancer (BC) is the most diagnosed cancer worldwide, mainly affecting the epithelial cells from the mammary glands. When it expresses the estrogen receptor (ER), the tumor is called luminal BC, which is eligible for endocrine therapy with hormone signaling blockade. Hormone therapy is essential for the survival of patients, but therapeutic resistance has been shown to be worrying, significantly compromising the prognosis. In this context, the need to explore new compounds emerges, especially compounds of plant origin, since they are biologically active and particularly promising. Natural products are being continuously screened for treating cancer due to their chemical diversity, reduced toxicity, lower side effects, and low price. This review summarizes natural compounds for the treatment of luminal BC, emphasizing the activities of these compounds in ER-positive cells. Moreover, their potential as an alternative to endocrine resistance is explored, opening new opportunities for the design of optimized therapies.